Activating AMPK to Restore Tight Junction Assembly in Intestinal Epithelium and to Attenuate Experimental Colitis by Metformin - Chen, Lu; Wang, Jie; You, Qian; He, Shuai; Meng, Qianqian; Gao, Jian; Wu, Xudong; Shen, Yan; Sun, Yang; Wu, Xuefeng; Xu, Qiang (Frontiers in Pharmacology, 2018)
Adenosine monophosphate-activated protein kinase (AMPK), a crucial molecule in energy metabolism, is reported to play a potential role in gut epithelial differentiation and barrier function recently; however, its performance and mechanisms in the pathological process of inflammatory bowel diseases remain unidentified. In this study, we have found that the phosphorylation of AMPK in colonic tissues is negatively correlated with severity of disease during the initiation and development of experimental colitis induced by dextran sulfate sodium. Activation of AMPK by metformin significantly controls the progression of colitis, which is associated with the maintenance of tight junction in colonic epithelium in mice. Moreover, our in vitro data in colonic epithelial Caco2 cells shows that metformin promotes expression and assembly of tight junctions via an AMPK-dependent way. Overall, our results suggested that activating AMPK by a clinically safe drug metformin could be a beneficial choice for colitis treatment.